Potensi Bungkil Inti Sawit Sebagai Campuran Media Tanam Pada Tanaman Tomat (Lycopersicum Escalantum Mill) - Dewi Amelia Widiyastuti; Nisa Salsabila (Jurnal Teknologi Agro-Industri, 2021)
Palm kernel meal or often referred to as (BIS) is one of the byproducts of processed palm oil in the manufacture of palm oil. The content of palm kernel cake (BIS) has fiber similar to the content in grass. Among other things containing less than 10% water, 14-17% protein, 9.5-10.5% fat and crude fiber 12-18%. Nutrition factions are cellulose, fat, protein, arabinoxilan, glucoronoxilan, and minerals. This material can be obtained by chemical processes or by mechanical means. So far, palm kernel cake (BIS) is widely used as animal feed because of the high protein contained therein, so it is very rarely used as a planting medium. This study aims to find the right composition in a mixture of palm kernel cake (BIS) which is good as a medium for planting a mixture of palm kernel cake (BIS) with mineral soil. In this study, the tomato nucleus (BIS) mixed tomato planting media had 4 treatments namely A0: without giving palm kernel cake (BIS), A1: 40 g palm kernel cake (BIS), A2: 50 g palm kernel cake (BIS), A3: 60 g palm kernel cake (BIS). The parameters measured were plant height growth and leaf blade growth based on the results of the study obtained, palm kernel cake has the potential to be one of the ingredients in making planting media. Keywords: Palm kernel cake (BIS), land application, tomato.